1986
DOI: 10.1002/cne.902490207
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical localization of urotensin I/corticotropin‐releasing factor, urotensin II, and serotonin immunoreactivities in the caudal spinal cord of nonteleost fishes

Abstract: Neurosecretory cells in the caudal spinal cord of fishes were first discovered in elasmobranches. However, most of the subsequent work on the caudal neurosecretory system has emphasized its morphology and function in teleosts. Two major peptides, urotensins I and II (UI and UII), have been isolated from this system in teleosts and their amino acid sequences have been determined. We have used immunohistochemical techniques to confirm and expand previous morphological and pharmacological findings regarding the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0
3

Year Published

1992
1992
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(12 citation statements)
references
References 35 publications
1
8
0
3
Order By: Relevance
“…Although nonteleost fish do not possess an authentic urophysis, they do exhibit a neurohemal area apposed to the ventral spinal cord that extends along several spinal cord segments (Fridberg and Bern, 1968). UII-immunoreactive cell bodies actually occur in the caudal spinal cord of representative species of nonteleost fish, including chondrichthyes (cartilaginous fish) and dipnoans (lungfish) but not agnatha (jawless fish) (Onstott and Elde, 1986).…”
Section: F the Urotensin II And Urotensin Ii-related Peptide Genesmentioning
confidence: 99%
“…Although nonteleost fish do not possess an authentic urophysis, they do exhibit a neurohemal area apposed to the ventral spinal cord that extends along several spinal cord segments (Fridberg and Bern, 1968). UII-immunoreactive cell bodies actually occur in the caudal spinal cord of representative species of nonteleost fish, including chondrichthyes (cartilaginous fish) and dipnoans (lungfish) but not agnatha (jawless fish) (Onstott and Elde, 1986).…”
Section: F the Urotensin II And Urotensin Ii-related Peptide Genesmentioning
confidence: 99%
“…The chemical nature of the neuronal inputs to the caudal neurosecretory system has been analyzed by various techniques including electron microscopy (O'Brien and Kriebel, 1983;Miller and Kriebel, 1986a) and immunohistochemistry (Miller and Kriebel, 1986b;Onstott and Elde, 1986;Yulis et al, 1990;Oka et al, 1997). With respect to the peptidergic innervation, we reported that NPY-positive fibers made occasional contact with UI-and/or UII-positive cells and fibers in several fishes and cyclostomes, strongly suggesting NPYergic afferent innervation of the Dahlgren cells (Oka et al, 1997).…”
Section: Introductionmentioning
confidence: 92%
“…The caudal neurosecretory system is a neuroendocrine system found in the posterior spinal cord of teleost and elasmobranch fishes. It has been identified in most teleostean fishes and in a few dipnoans (e.g., Kobayashi et al 1986;Onstott and Elde 1986). In 1914, Dahlgren described enlarged neurosecretory cells dispersed in the posterior region of the spinal cord in 11 species of skates (Dahlgren 1914), and subsequently Speidel named these enlarged neurosecretory cells after Dahlgren (Speidel 1922).…”
Section: Introductionmentioning
confidence: 97%